Tourism service design: promoting Malaysian culture through national identity at Kuala Lumpur International Airport - Phoon, Gar Chi (2019)
Airport is a great place to exhibit local values and the spirits of a country. The purpose ofthis study was to explore how airports can become a potentially an immersive space that evokes thelocal culture to create a sense of place for travellers. Nine international participants wereselected from Asia, Europe and America countries with different educational background. Qualitativedata collection methods included one month ethnographic observation, service design workshop andinterviews. The first phase of data collection methods consists of gaining customers’ insight fromvarious instruments such as persona, user journey map and role play simulation. These instrumentswere applied to understand the customer’s journey and user experience from a specific persona’sperspective. Followed by second phase, semi-structured interviews with a brand expert. The datawere analysed using a qualitative data analysis program, NVivo12, to develop ‘coding’ process.Results show introducing the Malaysian culture in the airport through showcasing video of localattractions; games and arts; local music; providing a taste of local food; promoting on Borneocultural features; providing local culture ambience; digitalisation; seasonal events; constructingidentity through festivals and utilising various local musical instruments. The implication of thisstudy will help the KLIA to promote our local culture and identity within the context of airportservice environment and becomesone of the most important tourists’ attractions for Malaysia.